Back to the future: A practice led transition program from Assistant in Nursing to Enrolled Nurse. (January 2017) - Faithfull-Byrne, Annette; Thompson, Lorraine; Welch, Tony; Williamson, Moira; Schafer, Keppel; Hallinan, Claire
Abstract: Continuing professional development is an essential element in professional nursing practice. In our Hospital and Health service, a gap in existing nursing pathways was identified for Assistants in Nursing (AINs), who wished to further their career in nursing and progress to Enrolled Nurse (EN). There is also little in the literature that addresses Assistants in Nursing wishing to progress their career to Enrolled Nurses. This article describes a quality improvement project designed to address this gap. The project was a collaborative venture between a Queensland Hospital and Health Service and an Institute of Tertiary and Further Education (TAFE). The focus was on creating a flexible career path for Assistants in Nursing, wishing to become Enrolled Nurses. The project resulted in the Diploma of Nursing program (theory and practice) being delivered within the hospital setting by nurse educators and clinical nurse consultants. This is unusual in that the program is normally delivered in the tertiary setting, by academic staff from the Institute of Further Education. Program implementation is described along with the challenges encountered. Outcomes from the project were: 78% completion rate; 100% employment on completion of their course of study; and 18% progressing to further their education such as Advance Enrolled Nurse or Registered Nurse. Student satisfaction regarding the program was also positive. The initiative established a local career path for Assistants in Nursing wishing to progress to Enrolled Nurse. This quality project demonstrates that collaborative ventures between the tertiary sector and hospital and health services, can create innovative flexible solutions for staff wishing to further their career in nursing. Highlights: Collaborative venture between the tertiary sector and a Hospital and Health Service. A flexible Diploma of Nursing program was delivered within an acute regional hospital for Assistants in Nursing to transition to Enrolled Nurses. Challenges were financial, role conflict and issues relating to academic study. 100% graduates from the program were employed. Some students progressed to Enrolled Nurse Advanced Practice or Registered Nurse.